ESTRO ACROP: Technology for precision small animal radiotherapy research: Optimal use and challenges - Verhaegen, Frank; Dubois, Ludwig; Gianolini, Stefano; Hill, Mark A.; Karger, Christian P.; Lauber, Kirsten; Prise, Kevin M.; Sarrut, David; Thorwarth, Daniela; Vanhove, Christian; Vojnovic, Boris; Weersink, Robert; et al. (Radiotherapy and Oncology, 2018)
Many radiotherapy research centers have recently installed novel research platforms enabling the investigation of the radiation response of tumors and normal tissues in small animal models, possibly in combination with other treatment modalities. Many more research institutes are expected to follow in the coming years. These novel platforms are capable of mimicking human radiotherapy more closely than older technology. To facilitate the optimal use of these novel integrated precision irradiators and various small animal imaging devices, and to maximize the impact of the associated research, the ESTRO committee on coordinating guidelines ACROP (Advisory Committee in Radiation Oncology Practice) has commissioned a report to review the state of the art of the technology used in this new field of research, and to issue recommendations. This report discusses the combination of precision irradiation systems, small animal imaging (CT, MRI, PET, SPECT, bioluminescence) systems, image registration, treatment planning, and data processing. It also provides guidelines for reporting on studies.